Simulation of a thermal environment in two buildings for the wet processing of coffee (2015)
This study aimed to compare the bioclimate and energy consumption of two coffee wet processing facilities in Colombia, with two typical types of Colombian coffee, using computer simulation. Specifically, we evaluated the effect of the heat generated by machines and the effect of the natural ventilation area on temperature and relative air humidity inside these buildings and their energy consumption. The postharvest plant with typology b gave the best results in terms of temperature and relative humidity suitable to preserve the quality of the coffee bean. Its approximate energy consumption was 30% of the total consumed by typology a.